Evidence of high individual variability in seed management by scatter-hoarding rodents: does 'personality' matter?. (April 2019) - Feldman, Mariano; Ferrandiz-Rovira, Mariona; Espelta, Josep Maria; Muñoz, Alberto
Abstract : The predation and dispersal of seeds by scatter-hoarding animals is one of the most studied processes in the context of animal–plant interactions. Seed management by these animals has been traditionally approached at the population level: the patterns documented in the field are assumed to be similar for all individuals of the population and the variability within the population is considered to be random noise. However, little is known about to what extent this variability responds to different and consistent behaviours between individuals. The aim of this study was to analyse the individual variation and consistency in behaviour of scatter-hoarding rodents within a population. As our model we used the wood mouse, Apodemus sylvaticus, a key disperser of holm oak acorns, Quercus ilex, which, in turn, suffers high predation pressure by the common genet, Genetta genetta . In two sets of laboratory experiments, we compared the variance and consistency in behaviours and acorn management due to individual differences with that due to manipulation, using genet scents, of the perceived predation risk. Genet scents reduced the activity (i.e. time out of the refuge) in all wood mice, but the differences and consistency in activity between individuals accounted for most of the variance. Also, mice showed different and consistent stress or relaxed behaviours. Most of the variance in seed management variables, such as dispersal distance and seed size selection, was explained by consistent differences between individuals across scent treatments. The increase in stress behaviours and decrease in relaxed behaviours were positively related to dispersal ability (i.e. longer distances and larger acorns). Our study highlights the importance of considering the individual component of behaviour in scatter-hoarding rodents. This fine-scale level, largely overlooked in the ecological framework, will help to increase our understanding of seed management by scatter-hoarding animals. Highlights: We analysed the individual variation in behaviour by scatter-hoarding rodents. The perceived predation risk was manipulated to assess the consistency of behaviour. Individual differences explained more than 80% of total behavioural variance. Rodents showed an extraordinary consistency in their individual behaviour. We highlight the relevance of individual behaviour in scatter-hoarding animals.